2011
DOI: 10.1002/hep.24340
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of phosphatase and tensin homolog by hepatitis C virus core 3a in hepatocytes triggers the formation of large lipid droplets

Abstract: Hepatitis C virus (HCV) perturbs the host's lipid metabolism and often results in hepatic steatosis. In nonalcoholic fatty liver disease, the intrahepatic down-regulation of phosphatase and tensin homolog deleted on chromosome 10 (PTEN) is a critical mechanism leading to steatosis and its progression toward fibrosis and hepatocellular carcinoma. However, whether an HCV infection triggers the formation of large lipid droplets through PTEN-dependent mechanisms is unknown. We assessed PTEN expression in the liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
61
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 34 publications
4
61
3
Order By: Relevance
“…[15] Secondly, another problem that is not well understood is the interaction between HCV and lipid metabolism. [16] So, HCV G3 selectively interferes with the late cholesterol synthesis pathway, [17] although this interference is resolved after the SVR. Other mechanisms that alter lipid metabolism are increased the novo lipogenesis and the inhibition of mitochondrial fatty acid degradation.…”
Section: Editorialmentioning
confidence: 99%
“…[15] Secondly, another problem that is not well understood is the interaction between HCV and lipid metabolism. [16] So, HCV G3 selectively interferes with the late cholesterol synthesis pathway, [17] although this interference is resolved after the SVR. Other mechanisms that alter lipid metabolism are increased the novo lipogenesis and the inhibition of mitochondrial fatty acid degradation.…”
Section: Editorialmentioning
confidence: 99%
“…Regarding the liver, we previously reported that PTEN is downregulated in steatotic livers of obese patients, as well as in rat models of genetic or diet-induced obesity [13]. Likewise, PTEN is downregulated in the liver of patients infected with hepatitis C virus (HCV) [14]. Interestingly, both obesity and HCV infection are associated with the development of steatosis and IR.…”
Section: Introductionmentioning
confidence: 99%
“…In support of a model where core plays a direct role in altering transcriptional events, core was shown to bind and activate the DNA-binding domain of the retinoid X receptor ␣, a transcriptional regulator involved in the regulation of cellular lipid synthesis (24). It was recently shown that genotype 3a core protein induces the formation of large lipid droplets in hepatoma cells by decreasing the expression of phosphatase and tensin homolog and insulin receptor substrate 1 (IRS-1) (25). IRS-1 has also been linked to the development of insulin resistance in HCV-infected patients in a genotype-specific manner; genotype 3a core causes IRS-1 degradation through down-regulation of peroxisome proliferator-activated receptor ␥ and up-regulation of suppressor of cytokine signal 7 (SOCS7), whereas genotype 1b core instead activates the mammalian target of rapamycin (mTOR) pathway (26).…”
mentioning
confidence: 98%